Concurrent Ce doping and in-situ carbon coating of Li2MnSiO4 nanoparticles with enhanced capacity via a rapid microwave-assisted sol-gel proces. (1st March 2021) - Ma, Dongwei; Feng, Yuanyuan; Zhang, Bo; Feng, Jijun; Pan, Jia Hong
Highlights: A specially designed microwave tube furnace is developed to rapidly synthesize Li2 Mn0.97 Ce0.03 SiO4 @C with tailored textural properties. The resulting Li2 Mn0.97 Ce0.03 SiO4 @C show a large surface area of 96.0 m 2 /g and particle size of 10–30 nm. Li2 Mn0.97 Ce0.03 SiO4 @C exhibits an ultrahigh initial discharge capacity of 210.5 mAh⋅g −1 with high coulomb efficiency ~90% at 0.1 C and the capacity remained 78.8 mAh⋅g −1 at 2C after 20 cycles. The superior performances of Li2 Mn0.97 Ce0.03 SiO4 @C are mainly derived from the excellent textural properties, surface carbon coating, and Ce 3+ doping. Abstract: We demonstrate a straightforward microwave-assisted sol-gel (MSG) process to facilely control the crystallization, ion doping and surface carbon coating synchronously for Li2 Mn1− x Ce x SiO4 @C (0 ≤  x  ≤ 0.05) nanoparticles (NPs) through tuning the velocity of inner gas and the microwave power. In our procedure, Ce 3+ ions are used as dopants and play a significant role in the microwave absorbent enhancement, and L-Ascorbic acid is used as the carbon source and the effective reductant to prevent the oxidization of Mn 2+ . Upon the MSG process, concurrent incorporation of Ce 3+ ions into the lattice sites of Li2 MnSiO4 and the in-situ carbonization of carbonaceous precursors can readily proceed. The optimal Li2 Mn0.97 Ce0.03 SiO4 @C NPs with a narrow particle size distribution in the range of 15–30 nm are demonstrated to show a high initial discharge capacity ~210.5 mAh⋅g −1 at 0.1C with a coulomb efficiency ~90%, and excellent rate performances at various current densities in the voltage range of 1.5-4.5 V. Graphical abstracts: Image, graphical abstract